Aspects of the Epigraphic Culture of Cannon Inscriptions during the Reign of Sigismund Augustus - Tolkačevski, Kšištof (Knygotyra, 2021)
Any object marked with epigraphic writing becomes unique in the totality of the same objects and acquires the status of a monument. In the 16th century, cannons were also marked with inscriptions (texts and images): some were created for warfare, others – to commemorate a certain event. During the reign of Sigismund Augustus, the Grand Duchy of Lithuania created the necessary infrastructure for cannon casting, which allowed it to produce large numbers of cannons to prepare for its war with the Grand Duchy of Moscow. The article attempts to reconstruct inscriptions on cannons using original and published archival sources stored in memory institutions in foreign countries (Poland, Sweden). An appendix covering 67 cannon records made it possible to perceive the structure of such inscriptions. Meanwhile, with the help of the ego-documentary legacy of the last Jagiellonian ruler, it was possible to study the functionality of cannon recordings in the context of epigraphic culture, paying special attention to the stages of the record’s emergence. This has so far been little studied at all. The collected data allowed to reach the conclusion that it was the ruler of the Grand Duchy of Lithuania who directly influenced the form, names, and content of the inscriptions on cannons.
Keywords: Sigismund Augustus; epigraphy; epigraphic culture; inscription; cannons